Developing a faith-based framework for ethical AI use in language classrooms: Teachers’ perceptions - Andriani, Erina (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The increasing use of artificial intelligence (AI) in education raises urgent ethical concerns, such as academic dishonesty, dependency on AI tools, and authenticity. Thus, the need for ethical guidance is growing, leading to AI ethical education. This phenomenon leads to the shift of teachers’ role as a guide in cultivating students’ ethical AI use. Religious values, such as Christian values, can offer a strong moral grounding to address such ethical challenges, especially in Indonesia, where the principle of divinity is strongly upheld through Pancasila and considered a key aspect of holistic learning. Christian values, such as honesty, responsibility, integrity, and stewardship, can be a moral compass for teachers in providing AI ethical education. However, few studies examined how faith-based values can inform practical classroom guidance on AI ethics. Therefore, this research aims to explore the teachers’ views on students’ ethical AI use and their strategies in guiding the students based on Christian values. Using a mixed-methods approach, data will be collected through surveys and interviews with language teachers using open-ended and closed-ended questionnaires and a semi-structured interview. The findings revealed the ethical concerns faced by teachers, their perceptions of the role as an ethical AI guide, and their faith-based framework in cultivating students’ ethical AI use. The significance of this study is to promote the use of religious values in fostering ethical awareness and to offer a clear, value-based framework in addressing AI ethics.